J/ψ-hadron correlations at midrapidity in pp collisions at √s = 13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; et al. (Journal of high energy physics, 2025)
We report on the measurement of inclusive, non-prompt, and prompt J/ψ-hadron correlations by the ALICE Collaboration at the CERN Large Hadron Collider in pp collisions at a center-of-mass energy of 13 TeV. The correlations are studied at midrapidity (|y| < 0.9) in the transverse momentum ranges pT < 40 GeV/c for the J/ψ and 0.15 < pT < 10 GeV/c and |η| < 0.9 for the associated hadrons. The measurement is based on minimum bias and high multiplicity data samples corresponding to integrated luminosities of Lint = 34 nb−1 and Lint = 6.9 pb−1, respectively. In addition, two more data samples are employed, requiring, on top of the minimum bias condition, a threshold on the tower energy of E = 4 and 9 GeV in the ALICE electromagnetic calorimeters, which correspond to integrated luminosities of Lint = 0.9 pb−1 and Lint = 8.4 pb−1, respectively. The azimuthally integrated near and away side yields of associated charged hadrons per J/ψ trigger are presented as a function of the J/ψ and associated hadron transverse momentum. The measurements are discussed in comparison to PYTHIA calculations.
The ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, M.W. Menzel, A. Nath, Y. Pachmayer, K. Reyers, R. Schicker, F. Schlepper, J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M.A. Völkl, B. Windelband, A. Yuncu, F. Zanone, B. Zhang und 1054 weitere
Gesehen am 14.01.2026